Protocol for Monitoring Tropical Forest Restoration - Viani, Ricardo A; Holl, Karen D; Padovezi Aurelio; Strassburg Bernardo B N; Farah, Fabiano T; Garcia, Letícia C; Chaves, Rafael B; Rodrigues, Ricardo R; Brancalion, Pedro H (Tropical conservation science, 2017)
Monitoring protocols are needed to evaluate the millions of hectares of land that are being proposed for forest restoration in the coming decades. Standardized proposals are critical to evaluate efficacy of restoration strategies, identify triggers for corrective actions, compare results across projects, and generally learn from past projects to inform future restoration efforts. We describe an iterative process, including over 200 stakeholders, to develop a protocol for monitoring Brazilian Atlantic Forest restoration. We give an overview of the ecological, socioeconomic, and management criteria, indicators, and metrics included in the protocol. Strengths of the protocol include the following: (a) testing and use across sites with a range of ages, forest types, past land uses, restoration techniques, and implementing institutions; (b) participation by a broad range of government, nongovernment, private, and academic institutions in the protocol development process; and (c) inclusion of socioeconomic and management criteria. Next steps for facilitating the broad adoption of the protocol in the Atlantic Forest region include providing in person and online training courses, establishing an online repository for storing and comparing monitoring data, and developing smartphone applications to facilitate data collection. Although the protocol was developed for the Atlantic Forest context and further refinements are needed, we think that the Atlantic Forest Pact monitoring protocol may serve as a model to inform the development of similar protocols in other regions, which ultimately could be integrated to produce a pantropical protocol for common use by several restoration forest programs worldwide.